MANAGEMENT OF TONSILLOLITH PALATINE: PENATALAKSANAAN BATU TONSILA PALATINA - Yohana, Winny (Dentika: Dental Journal, 2018)
Tonsillolith Palatine are stones that logded in tonsillar palatine crypt, tonsillolith are stones that caused by an accumulation of sulfur-producing bacteria, fungus, desquamated cells, food debris, and mucus that collect in the tonsillar crypts. Tonsillolith also known as tonsil stones, tonsillar concretion, or lith. Tonsilloliths have been recorded weighing from 0,3g to 4g. It may be difficult to remove, but are usually not harmful. Tonsillolith can be unilateral or bilateral. Occurs in young adult and are rare in children. Etiologi is unknown, it has been shown that the calcification develop with mass of desquamated epithelium cells, serum, food debris and bacterial colony. This case reports a patient with tonsillolith palatine. A -55 years-old female came to a private clinic, she complained difficult to swallow, sore throat, itching in right tonsillar, a foreign body-like sensation. On clinical examination, a superficial tonsillolith may be seen as white hard mass within the right tonsillar, tonsillar slightly inflammation. The tonsillolith size is 2x3x1mm. Treatment is usually removal of the tonsilliths by excavator and although mouthwash, clindamycin 300mg three times a day, diclofenac sodium 50mg three times a day, gargling helps wound healing. After tonsillith excavated , a week later the wound healing is well. Her right tonsil palatine looks healthy, wound healing is normal no sore throat, prognosis is good. Healing will be perfect when eating soft food. Successful treatment depends on good cooperation between the patient and the doctor. Keywords: tonsillolith palatine, sore throat, excavated